Implementation Of The Assossian Rule Mining (ARM) Method In The Sales Pattern Of Goods To Consumers In Stores Agung Bengkulu - Herrianto, David; Khairil, Khairil; Kanedi, Indra (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
Management of product sales data at Toko Agung Bengkulu is still done manually. There is no system that helps predict sales patterns for products that are in high demand and the problem that is often faced is the scarcity of supply of products that are in demand at Toko Agung. To make decisions in determining the amount of product inventory that can be adjusted to market demand, Toko Agung does not yet use a system and is still calculating manually. Therefore, this research was carried out with the aim of implementing the Association Rule Mining (ARM) method in grouping sales data at the Agung Store. So you can easily determine and classify high product sales. The system implementation uses the PHP programming language and MySQL database and the method used in this research is the waterfall method. After carrying out the Association Rule Mining (ARM) process at Toko Agung with data testing, the results obtained were the highest level of product sales at Toko Agung Bengkulu. This can be used as a reference by Toko Agung for product inventory for the following month.